Pharmacokinetics and residues elimination of diclofenac sodium administration in pigs by a new HPLC/MS method - Li, Yongjun; Yang, Haifeng; Wang, Yaqin; Bu, Shijin (Cellular and Molecular Biology, 2019)
Diclofenac sodium (DS) was the third generation non-steroidal drugs with analgesic and antipyretic properties. Owing to taking action faster, long lasting potency, good efficacy and low side effects, DS was widely used in the pharmaceutical industry. To further ensure animal food safety and consumer health, the rational usages regulations of DS and DS withdrawal time should be provided. In the present study, a new high performance liquid chromatography tandem mass spectrometry (HPLC/MS) method was first established for extracting and validating diclofenac sodium levels in edible porcine tissues. Meanwhile, the pharmacokinetics characteristics and residue elimination of intramuscular DS administration in pigs were also studied. We found DS eliminated quickly and the distribution was poor in vivo. After a single dose of 2.5 mg/kg body weight per day for continuous 3 days, the withdrawal time in the tissues of liver, kidney, sebum, muscle and administration site were 9.892 days, 5.116 days, 14.205 days, 5.444 days and 8.818 days, respectively. According to the double-sided 95% confidence interval, DS withdrawal period should be 15 days. These experiment evidences lay a good foundation on the rational usages regulations of DS and DS withdrawal time, which will be helpful for the animal food safety and consumer health.